Measuring relationships between self‐compassion, compassion fatigue, burnout and well‐being in student counsellors and student cognitive behavioural psychotherapists: a quantitative survey. Issue 1 (19th December 2015) - Beaumont, Elaine; Durkin, Mark; Hollins Martin, Caroline J.; Carson, Jerome
Abstract: Background: Prolonged deficiency in self‐care strategies puts counsellors and psychotherapists at risk of burnout and compassion fatigue. Aim: To measure associations between self‐compassion, compassion fatigue, well‐being and burnout in student counsellors and student cognitive behavioural psychotherapists. Method: A quantitative survey using four validated data collection instruments: (1) Professional Quality of Life Scale; (2) Self‐Compassion Scale; (3) short Warwick and Edinburgh Mental Well‐being Scale; (4) Compassion For Others scale, was used to measure relationships between self‐compassion, compassion fatigue, well‐being and burnout. Participants: A mixed sample of student counsellors and student cognitive behavioural psychotherapists ( n  = 54) in their final year of study. Results: This preliminary study shows that student counsellors and student cognitive behavioural psychotherapists who reported high on measures of self‐compassion and well‐being also reported less compassion fatigue and burnout. Implications for practice: Compassion fatigue and burnout are found in many modern‐day, highly stressful healthcare professions. The practice of self‐compassion could help student practitioners manage these symptoms and subsequently improve their professional quality of life. Abstract : A video abstract of this article can be viewed at:https://vimeo.com/150762974